Semi-rigid and semi-flexible light steel bridge deck pavement structure and pavement method thereof
By using lightweight aggregates and modified epoxy resin materials in the steel bridge deck paving structure, a semi-hard and semi-flexible lightweight steel bridge deck paving structure is prepared, which solves the problem of high temperature and deformation of the steel bridge deck. Fatigue cracks and other problems have improved load-bearing capacity and durability, and achieved lightweight structures and energy-saving and environmentally friendly.
Patent Information
- Application Number
- CN202411587441.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing steel bridge deck paving technology, the steel bridge deck structure is prone to high temperature, deformation, fatigue cracks and other problems, and its load-bearing capacity and durability are not satisfactory.
Using a semi-hard and semi-flexible lightweight steel bridge deck paving structure, the cast asphalt concrete underlayer with excellent performance and low density is prepared by replacing ordinary aggregates by using lightweight aggregates and lightweight fillers, and the lower layer of cast asphalt concrete with excellent performance and low density is prepared and modified Epoxy resin cement, granite asphalt and other raw materials are made into lightweight modified epoxy asphalt concrete as the upper layer to form a synergistic paving structure.
It improves the stress performance of the steel bridge deck, enhances the load-bearing capacity and durability of the paved structure, improves the road performance, and realizes the lightweight and energy-saving and environmentally friendly structure.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel bridge deck pavement, and in particular to a semi-rigid and semi-flexible lightweight steel bridge deck pavement structure and a paving method thereof. Background Art
[0002] In recent years, the scale of infrastructure construction in my country has increased year by year, and the scale of steel plate bridge construction has also become larger and larger, and has gradually developed in the direction of crossing the sea and crossing the river. At present, with the large-scale construction of steel plate bridges, due to the characteristics of the steel bridge deck structure itself, not only the pavement layer of the steel bridge deck is often in a high temperature state, the concrete performance cannot be fully exerted, but also due to the large flexibility of the steel box girder, the pavement layer is prone to large deformation, fatigue cracks and other hazards; in addition, due to the constant load limit of the upper pavement structure, the pavement structure should not be too thick, and the bearing capacity and durability of the steel bridge deck are not satisfactory.
[0003] In view of the defects existing in the existing steel bridge deck paving technology, the inventor has used his rich practical experience and professional knowledge in the design and manufacture of such products for many years, and combined with the application of science, he actively carried out research and innovation, in order to create a semi-rigid and semi-flexible lightweight steel bridge deck paving structure and its paving method. The paving structure replaces ordinary aggregates with lightweight aggregates, and controls the aggregate particle size for multiple grading combinations to prepare a cast asphalt concrete bottom layer with excellent performance and low density; at the same time, by adding admixtures and lightweight fillers to the binder, the viscosity is increased while reducing its own density; finally, modified epoxy resin binder, qinggang asphalt and other raw materials are used to make lightweight modified epoxy asphalt concrete as the upper layer that is resistant to high temperature and has good deformation tracking properties, so as to form a semi-rigid and semi-flexible steel bridge deck paving structure. Through reasonable material innovation and structural design, the present invention improves the stress performance of the steel bridge deck, improves the bearing capacity and durability of the paving structure, and makes the overall structure have better road performance. After continuous research, design, repeated trial production and improvement, we finally created this invention which is truly of practical value. Summary of the invention
[0004] The first purpose of the present invention is to provide a semi-rigid and semi-flexible lightweight steel bridge deck pavement structure, which can reduce the overall structure's own dead load and improve the stress performance of the steel panel while improving the performance in use; at the same time, based on the density difference between the lightweight material and the mixture, the structural layer has better deformation tracking properties and ensures effective bonding between the structural layer and the steel bridge deck; in addition, based on the synergistic effect of the rigid upper layer, the flexible lower layer and the steel panel, a semi-rigid and semi-flexible pavement structure is formed, which improves the structure in terms of strength, rigidity, high temperature stability, crack resistance and anti-slip performance, increases the durability of the structure, improves the road performance, and achieves energy saving and environmental protection.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions:
[0006] The present invention provides a semi-rigid and semi-flexible lightweight steel bridge deck pavement structure, which comprises, from bottom to top of the steel plate, an anti-rust layer, a waterproof bonding layer, a lightweight flexible cast asphalt concrete lower layer, a high-viscosity lightweight epoxy resin bonding layer and a lightweight modified epoxy asphalt concrete upper layer.
[0007] Furthermore, the total thickness of the pavement structure is 5 to 8 cm;
[0008] Furthermore, the thickness of the lower layer of lightweight flexible cast asphalt concrete is 3 to 4.5 cm, and the thickness of the upper layer of lightweight modified epoxy asphalt concrete is 2 to 3.5 cm.
[0009] Furthermore, calculated by weight, the lower layer of lightweight flexible poured asphalt concrete includes the following components: 5 to 15 parts of poured asphalt binder, 75 to 85 parts of mineral material, 1 to 4 parts of composite fiber and 0.3 to 1.2 parts of natural mineral powder type warm mix agent; the mineral material includes mineral powder, lightweight aggregate and ordinary aggregate.
[0010] Furthermore, the particle density of lightweight aggregate is 1.0 to 1.7 t / m 3 , mixture density 1.7~2.6t / m 3 Due to the density difference between lightweight materials and ordinary aggregates, the upper and lower layers of the structure are enriched with lightweight aggregates and ordinary aggregates respectively. At the same time, based on the characteristics of lightweight materials such as tiny pores, small expansion and contraction coefficients, and excellent thermal shock stability, the structure can achieve the transformation from "density difference" to "neutral expansion and contraction deformation". The thermal expansion of the overall structure is close to that of the steel plate, making the concrete layer have better deformation tracking properties.
[0011] Furthermore, the aggregate density difference range is 0.5~1.8t / m 3 (density ratio 0.45~1.0). If the density difference is larger (density ratio is close to 0), the microstructure homogeneity is poor, which affects the macroscopic mechanical strength and of the mixture; if the density difference is smaller (density ratio is close to 1), the neutralization expansion and contraction and lightweight effect are not obvious.
[0012] Furthermore, the ratio of glue to aggregate is controlled at 0.08-0.27, and the ratio of lightweight aggregate to ordinary aggregate is controlled at 0.6-1.5, so as to adjust the density of the mixture and achieve a suitable density difference.
[0013] Furthermore, the pouring asphalt binder is composed of SBS modified asphalt and lake asphalt in a mass ratio of (6.5:3.5) to (8:2). The higher the content of lake asphalt in the binder, the better the high temperature durability of the mixture. However, if the content of lake asphalt is increased blindly, the fluidity of the mixture will be impaired. The mass ratio in the present invention takes into account the characteristics of the two asphalts, so that their respective advantages can be fully utilized.
[0014] Furthermore, the composite fiber is composed of one or more of steel fiber, carbon fiber, glass fiber, polypropylene fiber, nylon fiber and plant fiber, and has a length of 5 to 15 mm and a diameter of 0.1 to 0.5 mm.
[0015] Furthermore, the lightweight flexible cast asphalt mixture is divided into particle gradation levels using sieve hole diameters of 0.075-0.15 mm, 0.6-1.18 mm, 2.36-4.75 mm and 9.5-13.2 mm as dividing lines to achieve multiple gradation combinations.
[0016] Furthermore, the crushed stone spread on the lower layer of lightweight flexible cast asphalt concrete is composed of one or more of granite, basalt or diabase, the crushed stone particle size is 12 to 18 mm, and the spreading amount is 8 to 12 kg / m 2 .
[0017] Furthermore, the high-viscosity lightweight epoxy resin bonding layer includes component A and component B. Calculated by weight, component A includes the following ingredients: 50 to 110 parts of bisphenol A or bisphenol B epoxy resin, 5 to 25 parts of toluene glycidyl ether active diluent, 2 to 4 parts of aluminate active coupling agent, and 0.3 to 2 parts of polyether defoaming agent; component B includes the following ingredients: 45 to 120 parts of epoxy resin toughening curing agent, 65 to 130 parts of matrix asphalt, 8 to 20 parts of polypropylene glycol diglycidyl ether active toughening agent, and 3 to 10 parts of lightweight filler.
[0018] Furthermore, the lightweight filler is composed of any one or more of lightweight calcium carbonate, expanded perlite, hollow glass microspheres, natural coal gangue and clay ceramsite. By adding lightweight fillers to the mixture, not only the overall density of the structure is reduced, but also the economic cost can be controlled.
[0019] Furthermore, calculated by weight, the upper layer of lightweight modified epoxy asphalt concrete includes the following components: 2 to 10 parts of modified epoxy resin binder, 10 to 15 parts of epoxy asphalt, 5 to 8 parts of granite asphalt, 15 to 140 parts of ordinary aggregate, 12 to 120 parts of lightweight aggregate, and 17 to 35 parts of mineral powder; the modified epoxy resin binder is made of bisphenol A or bisphenol B epoxy resin and modified amine curing agent in a mass ratio of 4 to 5:1.
[0020] Furthermore, the mineral powder in the concrete layer is ground from limestone; the lightweight aggregate is divided into light coarse aggregate and light fine aggregate, which is composed of 700-grade porous volcanic rock ceramsite, wherein the particle size range of the light coarse aggregate is 6 to 15 mm, and the particle size range of the light fine aggregate is 0 to 5 mm; the ordinary aggregate is formed by crushing basalt, and the mass percentage of the lightweight aggregate replacing the ordinary aggregate is 1% to 99%.
[0021] Furthermore, the oil-stone ratio of the lightweight modified epoxy asphalt concrete is 5 to 12%. By controlling the oil-stone ratio, the balance of skid resistance and durability of the upper structure is optimized.
[0022] The second object of the present invention is to provide a paving method for a semi-rigid and semi-flexible lightweight steel bridge deck pavement structure, which is characterized by the following specific implementation steps:
[0023] S1. Sandblast the steel plate to remove rust, so as to obtain a steel plate with a cleanliness greater than Sa2.5 and a roughness of 70 to 150 μm, and then spray an epoxy zinc-rich anti-rust paint with a thickness of 80 to 150 μm;
[0024] S2. After the bonding strength of the epoxy zinc-rich anti-rust paint is greater than 7MPa, clean the surface and apply epoxy resin adhesive type II to form a waterproof bonding layer. The coating amount is 0.4-0.5kg / m 2 ;
[0025] S3. Prepare lightweight flexible poured asphalt concrete, and then evenly spread it on the waterproof bonding layer with a thickness of 3 to 4.5 cm by a paver. The longitudinal spacing between the pavers is 5 to 20 m, the paving rate is 1.8 to 3.0 m / min, and the paving temperature is controlled at above 160°C. For local areas where machinery cannot operate, manual paving is used;
[0026] S4. Use a mixed asphalt consisting of modified asphalt and lake asphalt to wrap the crushed stones with a particle size of 12 to 18 mm. 2 The amount of asphalt is evenly spread on the surface of lightweight flexible cast asphalt concrete, and then rolled 2 to 4 times with a 20 to 30 t rubber-wheel roller to make the crushed stones half embedded in the concrete layer; wherein the mixed asphalt accounts for 0.3 to 1.5% of the mass of the crushed stones;
[0027] S5. Prepare a highly viscous lightweight epoxy resin adhesive. After the lower layer of lightweight flexible cast asphalt concrete cools and hardens, apply 0.5-0.9 kg / m 2 Apply the adhesive evenly with a spreading amount;
[0028] S6. Prepare lightweight modified epoxy asphalt concrete and spread it evenly with a paver in a thickness of 2 to 3.5 cm on the lower layer of lightweight flexible cast asphalt concrete coated with a high-viscosity lightweight epoxy resin binder. Then use a 18 to 30 t steel or rubber wheel roller to compact it 6 to 9 times to complete the rolling. Finally, carry out 2 to 7 days of maintenance according to the changes in the rebound strength value of the concrete. When the rebound strength value stabilizes at 40 to 60 MPa, it can be opened to traffic.
[0029] In summary, the beneficial effects of the present invention are:
[0030] 1. The present invention uses lightweight aggregates and lightweight fillers in the pavement structure to replace the original ordinary aggregates and fillers, thereby achieving lightweight structural layers, reducing the weight of the steel bridge deck by 20% to 60% while keeping the pavement thickness unchanged, and saving a large amount of high-quality aggregates.
[0031] 2. The present invention utilizes the density difference between lightweight materials and ordinary aggregates to form a gradient difference in the longitudinal direction of the pavement structure, thereby improving the shear resistance of the structure. It also fully utilizes the characteristics of lightweight materials such as small expansion and contraction coefficient, excellent thermal shock stability, and tiny pores inside, so that the overall structure has good deformation conformity and effectively suppresses the hazard of structural cracking. At the same time, composite fibers are added to the lightweight flexible poured asphalt concrete to improve its crack resistance, anti-skid and other properties, thereby reinforcing the pavement structure.
[0032] 3. The present invention adds materials such as SBS modified asphalt and granite asphalt into lightweight flexible poured asphalt concrete and lightweight modified epoxy asphalt concrete, thereby enhancing the overall high-temperature stability of the pavement structure, ensuring the high-temperature bearing capacity of the pavement structure, and improving driving comfort, providing a pavement structure with low dead weight and excellent performance for steel bridge deck pavement. DETAILED DESCRIPTION
[0033] In order to further explain the technical means and effects adopted by the invention to achieve the predetermined purpose of the invention, a semi-rigid and semi-flexible lightweight steel bridge deck pavement structure and its construction method proposed in accordance with the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.
[0034] The sources of raw materials in the embodiment are as follows:
[0035] SBS modified asphalt: Jiangsu Zhongyitong Road New Materials Co., Ltd.;
[0036] TLA Lake Asphalt: Jiangsu Zhongyitong Road New Materials Co., Ltd.;
[0037] HRM epoxy asphalt: Jiangsu Zhongyitong Road New Materials Co., Ltd.;
[0038] Qinggang asphalt: Zhonglu Jiaoke Technology Co., Ltd.;
[0039] 70# matrix asphalt: Jiangsu Zhongyitong Road New Materials Co., Ltd.;
[0040] Limestone powder: Tongzhou District Xingdong Lingchang Building Materials Business Department;
[0041] Rock gravel: Jiangsu Maodi Group Co., Ltd.;
[0042] Limestone filler: Jiangsu Maodi Group Co., Ltd.;
[0043] Lightweight filler: Jiangsu Maodi Group Co., Ltd.
[0044] Basalt aggregate: Jiangsu Maodi Group Co., Ltd.;
[0045] 5~25mm porous volcanic rock ceramsite: Yixing Tuhua Environmental Protection Co., Ltd.;
[0046] Epoxy resin adhesive type II: Zhonglu Jiaoke Technology Co., Ltd.;
[0047] Straight copper-coated steel fiber: Shanghai Harex Steel Fiber Technology Co., Ltd.;
[0048] Polypropylene fiber: Tai'an Daiyue Aixin Engineering Materials Co., Ltd.;
[0049] Natural mineral powder type warm mix agent: China Road and Transportation Science and Technology Co., Ltd.;
[0050] E42 bisphenol A epoxy resin: Shanghai MacLean Biochemical Technology Co., Ltd.; low-chlorine toluene glycidyl ether active diluent: Shanghai Fushun International Trade Co., Ltd.; HY-985 aluminate active coupling agent: Hangzhou Jessica Chemical Co., Ltd.;
[0051] DL-150 polyether defoamer: Jinan Delan Chemical Co., Ltd.
[0052] SK-302 modified amine curing agent: Zhonglu Jiaoke Technology Co., Ltd.;
[0053] H-type epoxy resin toughening curing agent: China Road and Transportation Science and Technology Co., Ltd.;
[0054] 207 polypropylene glycol diglycidyl ether active toughening agent: Jining Huakai Resin Co., Ltd.
[0055] Example 1
[0056] The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure provided in this embodiment comprises, from bottom to top, an anti-rust layer, a waterproof bonding layer, a lightweight flexible cast asphalt concrete lower layer, a high-viscosity lightweight epoxy resin bonding layer, and a lightweight modified epoxy asphalt concrete upper layer; the overall thickness of the structure is 6.5 cm, of which the thickness of the lightweight flexible cast asphalt concrete lower layer is 3.5 cm, and the thickness of the lightweight modified epoxy asphalt concrete upper layer is 3 cm;
[0057] The lower layer of lightweight flexible cast asphalt concrete includes the following components by weight: 10 parts of cast asphalt binder, 78 parts of mineral material, 2 parts of composite fiber and 0.4 parts of warm mix agent; the mass ratio of SBS modified asphalt and lake asphalt in the cast asphalt binder is 7:3; the composite fiber is steel fiber and polypropylene fiber with a length of 8 mm and a diameter of 0.2 mm; the mineral material includes mineral powder, lightweight aggregate and ordinary aggregate;
[0058] Among them, for lightweight flexible cast asphalt mixture, the particle size of 0.075-0.15mm accounts for 25%, the particle size of 0.6-1.18mm accounts for 30%, the particle size of 2.36-4.75mm accounts for 40%, and the particle size of 9.5-13.2mm accounts for 5%;
[0059] The lower layer of lightweight flexible cast asphalt concrete is spread with granite crushed stone, the crushed stone particle size is 12-18mm, and the spreading rate is 10kg / m 2 ;
[0060] The high-viscosity lightweight epoxy resin bonding layer includes component A and component B. Calculated by weight, component A includes the following ingredients: 60 parts of bisphenol A epoxy resin, 9 parts of toluene glycidyl ether active diluent, 2 parts of aluminate active coupling agent, and 0.8 parts of polyether defoamer; component B includes the following ingredients: 60 parts of epoxy resin toughening curing agent, 75 parts of matrix asphalt, 8 parts of polypropylene glycol diglycidyl ether active toughening agent, and 5 parts of lightweight filler; wherein the lightweight filler is light calcium carbonate;
[0061] The upper layer of lightweight modified epoxy asphalt concrete includes the following components by weight: 7 parts of modified epoxy resin binder, 12 parts of epoxy asphalt, 5 parts of granite asphalt, 112 parts of ordinary aggregate, 98 parts of lightweight aggregate, and 20 parts of mineral powder; wherein the modified epoxy resin binder is prepared by bisphenol A epoxy resin and modified amine curing agent in a mass ratio of 4:1;
[0062] The mineral powder is ground from limestone; the lightweight aggregate is divided into light coarse aggregate and light fine aggregate, which is composed of crushed stone type 700 grade porous volcanic rock ceramsite, wherein the particle size of the light coarse aggregate is in the range of 6 to 15 mm, and the particle size of the light fine aggregate is in the range of 0 to 5 mm; the ordinary aggregate is formed by crushing basalt, and the mass percentage of the lightweight aggregate replacing the ordinary aggregate is 38%;
[0063] Among them, the oil-to-stone ratio of lightweight modified epoxy asphalt concrete is 8%;
[0064] Among them, the lightweight rigid-flexible composite steel bridge deck pavement structure uses epoxy resin adhesive type II as the waterproof bonding layer, with a coating amount of 0.45kg / m 2 ;
[0065] Among them, the lightweight rigid-flexible composite steel bridge deck pavement structure uses a high-viscosity lightweight epoxy resin adhesive to bond the upper and lower layers, with a coating amount of 0.65kg / m 2 .
[0066] The paving method of the semi-rigid and semi-flexible lightweight steel bridge deck pavement structure provided in this embodiment has the following paving steps:
[0067] S1. Sandblast the steel plate to remove rust, so as to obtain a steel plate with a cleanliness greater than Sa2.5 and a roughness of 80 μm, and then spray 90 μm thick epoxy zinc-rich anti-rust paint;
[0068] S2. After the bonding strength of the epoxy zinc-rich anti-rust paint is greater than 7MPa, the surface is cleaned and the surface is treated with 0.45kg / m 2 Apply epoxy resin adhesive type II with a coating amount of , and then cure at room temperature for 36 hours to form a waterproof bonding layer;
[0069] S3. Prepare lightweight flexible cast asphalt concrete. Add porous volcanic rock ceramsite aggregate, basalt aggregate, mineral powder, steel fiber and polypropylene fiber in the lightweight flexible cast concrete into a high-temperature mixing pot at about 260°C in a certain order. After dry mixing for 90 seconds, evenly mix the additives into the binder and pour into the mixing pot. Mix at high temperature for 70 minutes to obtain lightweight flexible cast asphalt concrete.
[0070] S4. After the mixture is transported to the site by an insulated transport vehicle, it is evenly spread on the waterproof bonding layer with a thickness of 3.5 cm using a paver. The longitudinal spacing between the pavers is 5 to 20 m, the paving rate is 1.8 to 3.0 m / min, and the paving temperature is controlled above 160°C. For local areas where machinery cannot operate, manual paving is used;
[0071] S5. Use a mixture of modified asphalt and lake asphalt to coat granite crushed stones with a particle size of 12 to 18 mm, with the mixed asphalt accounting for 0.7% of the mass of the crushed stones. 2 The amount of crushed stone is evenly spread on the surface of lightweight flexible cast asphalt concrete, and rolled twice with a 27t rubber-wheel roller to make the crushed stone half embedded in the concrete layer. Finally, it is cured at room temperature for 36 hours to form the lower layer of lightweight flexible cast asphalt concrete.
[0072] S6. Prepare a high-viscosity lightweight epoxy resin binder. The high-viscosity lightweight epoxy resin binder includes component A and component B. When preparing, first take bisphenol A epoxy resin, toluene glycidyl ether active diluent, aluminate active coupling agent, and polyether defoamer, place them in a mixer and stir them evenly for 4 hours to complete the preparation of component A; take matrix asphalt and heat it to a molten state, and at the same time take epoxy resin toughening curing agent for preheating, and pour polypropylene glycol diglycidyl ether active toughening agent and light calcium carbonate filler and molten asphalt and curing agent into a mixer and stir them evenly for 4 hours to complete the preparation of component B; mix component A and component B evenly and stir for 5 to 10 minutes to obtain a high-viscosity lightweight epoxy resin binder;
[0073] S7. After the lower layer of lightweight flexible cast asphalt concrete has cooled and hardened, 2 Apply the adhesive evenly with a coating amount;
[0074] S8. Prepare lightweight modified epoxy asphalt concrete. Dry mix mineral powder, basalt aggregate and porous volcanic rock expanded clay aggregate at a mixing station for 45 seconds. Then add modified epoxy resin binder, epoxy asphalt and qinggang asphalt and wet mix for 120 seconds to complete the production of lightweight modified epoxy asphalt concrete. Use a paver to evenly pave the lightweight modified epoxy asphalt concrete according to the thickness standard of 3 cm, and use an 18t steel wheel roller to roll it twice for the first time, then use a 27t rubber wheel roller to roll it four times, and finally use an 18t steel wheel roller to roll it twice for the final time before curing. Finally, according to the change of the concrete rebound strength value, it is cured for 2 to 7 days. When the rebound strength value stabilizes at 40 to 60MPa, it can be opened to traffic.
[0075] Example 2
[0076] The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure provided in this embodiment comprises, from bottom to top, an anti-rust layer, a waterproof bonding layer, a lightweight flexible cast asphalt concrete lower layer, a high-viscosity lightweight epoxy resin bonding layer, and a lightweight modified epoxy asphalt concrete upper layer; the overall thickness of the structure is 7.5 cm, of which the thickness of the lightweight flexible cast asphalt concrete lower layer is 4.0 cm, and the thickness of the lightweight modified epoxy asphalt concrete upper layer is 3.5 cm;
[0077] Among them, the lower layer of lightweight flexible cast asphalt concrete includes the following components by weight: 13 parts of cast asphalt binder, 82 parts of mineral material, 3.5 parts of composite fiber and 0.9 parts of warm mix agent; among them, the mass ratio of SBS modified asphalt and lake asphalt in the cast asphalt binder is 7.5:2.5; among them, the composite fiber is steel fiber and carbon fiber, with a length of 12mm and a diameter of 0.35mm; among them, the mineral material includes mineral powder, lightweight aggregate and ordinary aggregate;
[0078] Among them, for lightweight flexible cast asphalt mixture, the particle size is 0.075-0.15mm accounting for 37%, the particle size is 0.6-1.18mm accounting for 25%, the particle size is 2.36-4.75mm accounting for 32%, and the particle size is 9.5-13.2mm accounting for 6%;
[0079] The lower layer of lightweight flexible cast asphalt concrete is spread with basalt crushed stone, the crushed stone particle size is 12-18mm, and the spreading amount is 12kg / m 2 ;
[0080] Among them, the high-viscosity lightweight epoxy resin bonding layer includes component A and component B. Calculated by weight, component A includes the following ingredients: 87 parts of bisphenol F epoxy resin, 19 parts of toluene glycidyl ether active diluent, 3 parts of aluminate active coupling agent, and 1.3 parts of polyether defoamer; component B includes the following ingredients: 79 parts of epoxy resin toughening curing agent, 83 parts of matrix asphalt, 12 parts of polypropylene glycol diglycidyl ether active toughening agent, and 7 parts of lightweight filler; among them, the lightweight filler is clay ceramsite;
[0081] The upper layer of lightweight modified epoxy asphalt concrete includes the following components by weight: 9 parts of modified epoxy resin binder, 14 parts of epoxy asphalt, 7 parts of granite asphalt, 132 parts of ordinary aggregate, 114 parts of lightweight aggregate, and 25 parts of mineral powder; wherein the modified epoxy resin binder is prepared by bisphenol F epoxy resin and modified amine curing agent in a mass ratio of 4.2:1;
[0082] The mineral powder is ground from limestone; the lightweight aggregate is divided into light coarse aggregate and light fine aggregate, which are composed of crushed stone type 700 grade porous volcanic rock ceramsite, wherein the particle size of the light coarse aggregate is in the range of 6 to 15 mm, and the particle size of the light fine aggregate is in the range of 0 to 5 mm; the ordinary aggregate is formed by crushing basalt, and the mass percentage of the lightweight aggregate replacing the ordinary aggregate is 53%;
[0083] Among them, the oil-to-stone ratio of lightweight modified epoxy asphalt concrete is 9.2%;
[0084] Among them, the lightweight rigid-flexible composite steel bridge deck pavement structure uses epoxy resin adhesive type II as the waterproof bonding layer, with a coating amount of 0.5kg / m 2 ;
[0085] Among them, the lightweight rigid-flexible composite steel bridge deck pavement structure uses a high-viscosity lightweight epoxy resin adhesive to bond the upper and lower layers, with a coating amount of 0.8kg / m 2 .
[0086] The paving method of the semi-rigid and semi-flexible lightweight steel bridge deck pavement structure provided in this embodiment has the following paving steps:
[0087] S1. Sandblast the steel plate to remove rust, so as to obtain a steel plate with a cleanliness greater than Sa2.5 and a roughness of 85 μm, and then spray epoxy zinc-rich anti-rust paint with a thickness of 120 μm;
[0088] S2. After the surface of the epoxy zinc-rich anti-rust paint is dry, clean the surface and 2 Apply epoxy resin adhesive type II with a coating amount, and then cure at room temperature for 36 hours to form a waterproof bonding layer.
[0089] S3. Prepare lightweight flexible cast asphalt concrete. Add porous volcanic rock ceramsite aggregate, basalt aggregate, mineral powder, steel fiber and carbon fiber in the lightweight flexible cast concrete into a high-temperature mixing pot at about 260°C in a certain order. After dry mixing for 90 seconds, evenly mix the additives into the binder and pour into the mixing pot. Mix at high temperature for 70 minutes to obtain lightweight flexible cast concrete.
[0090] S4. After the mixture is transported to the site by an insulated transport vehicle, it is evenly spread on the waterproof bonding layer with a thickness of 4.0 cm by a paver. The longitudinal spacing between the pavers is 5 to 20 m, the paving rate is 1.8 to 3.0 m / min, and the paving temperature is controlled above 160°C. For local areas where machinery cannot operate, manual paving is used;
[0091] S5. Use a mixture of modified asphalt and lake asphalt to coat basalt crushed stones with a particle size of 12 to 18 mm, with the mixed asphalt accounting for 1.0% of the mass of the crushed stones. 2 The amount of crushed stone is evenly spread on the surface of lightweight flexible cast asphalt concrete, and rolled twice by a 25t rubber-wheel roller to make the crushed stone half embedded in the concrete layer, and finally cured at room temperature for 36 hours to form the lower layer of lightweight flexible cast asphalt concrete;
[0092] S6. Prepare a high-viscosity lightweight epoxy resin binder. The high-viscosity lightweight epoxy resin binder includes component A and component B. When preparing, first take bisphenol F epoxy resin, toluene glycidyl ether active diluent, aluminate active coupling agent, and polyether defoamer, place them in a mixer and stir them evenly for 4 hours to complete the preparation of component A; take matrix asphalt and heat it to a molten state, and at the same time take epoxy resin toughening curing agent for preheating, and pour polypropylene glycol diglycidyl ether active toughening agent, clay ceramsite filler, molten asphalt and curing agent into a mixer and stir them evenly for 4 hours to complete the preparation of component B; mix component A and component B evenly and stir for 5 to 10 minutes to obtain a high-viscosity lightweight epoxy resin binder;
[0093] S7. After the lower layer of lightweight flexible cast asphalt concrete has cooled and hardened, 2 Apply the adhesive evenly with a coating amount;
[0094] S8. Prepare lightweight modified epoxy asphalt concrete. Dry mix mineral powder, basalt aggregate and porous volcanic rock expanded clay aggregate at a mixing station for 45 seconds. Then add modified epoxy resin binder, epoxy asphalt and qinggang asphalt for wet mixing for 120 seconds to complete the production of lightweight modified epoxy asphalt concrete. Use a paver to evenly pave the lightweight modified epoxy asphalt concrete according to the thickness standard of 3.5 cm. Then use a 21t steel wheel roller to perform initial compaction twice, then use a 25t rubber wheel roller to perform re-compaction five times, and finally use a 21t steel wheel roller to perform final compaction twice before curing. Finally, perform curing for 2 to 7 days according to the change of the concrete rebound strength value. When the rebound strength value stabilizes at 40 to 60 MPa, it can be opened to traffic.
[0095] Comparative Example 1
[0096] When configuring the pavement structure, lightweight aggregates and fillers are replaced with commonly available commercial materials, and other configuration components and processes are consistent with Example 2.
[0097] Comparative Example 2
[0098] The high-viscosity lightweight epoxy resin adhesive in Comparative Example 1 was replaced with epoxy resin adhesive type II, and the remaining materials and configuration methods were consistent with Comparative Example 1.
[0099] The performance of the semi-rigid and semi-flexible lightweight steel bridge deck pavement structures in the above two embodiments and two comparative pavement structures were tested, and the specific index parameters are shown in Tables 1 to 3 below.
[0100] Table 1 Performance parameters of lightweight flexible cast asphalt concrete
[0101]
[0102] Table 2 Performance parameters of lightweight modified epoxy asphalt concrete
[0103]
[0104] Table 3 Performance parameters of high viscosity modified epoxy adhesive
[0105]
[0106]
[0107] According to Tables 1 to 3 above, the main advantages of the present invention as a semi-rigid and semi-flexible lightweight steel bridge deck pavement structure are:
[0108] (1) The relative density of the gross volume of the pavement structure is reduced by about 23.2%, which reduces the dead load of the overall structure and improves the stress characteristics of the steel bridge deck;
[0109] (2) The rutting dynamic stability at 60°C is greater than 20,000, an increase of about 33.3%, indicating that the high-temperature stability of the pavement structure has been significantly improved;
[0110] (3) Under the conditions closest to the pavement service state (15°C, 10Hz), the dynamic modulus is only 50.1% of the proportion, indicating that the pavement structure of the present invention has good deformation performance and can be well deformed in coordination with the steel panel;
[0111] (4) The friction coefficient of the pavement structure surface of the present invention is greater than 70BPN, and the structural depth is greater than 1mm, indicating that the semi-rigid and semi-flexible lightweight steel bridge deck pavement structure provided by the present invention has good anti-slip performance;
[0112] (5) The interlaminar pull-out strength at 20°C in the present invention is increased by an average of about 16%, and the pull-out strength at 60°C is increased by an average of about 32%, indicating that the high-viscosity lightweight epoxy resin adhesive in the present invention has a strong viscosity-increasing effect.
[0113] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A semi-rigid and semi-flexible lightweight steel bridge deck pavement structure, characterized in that: The total thickness of the pavement structure is 5~8cm. Starting from the steel plate, from bottom to top, it is composed of an anti-rust layer, a waterproof bonding layer, a lightweight flexible poured asphalt concrete lower layer, a high-viscosity lightweight epoxy resin bonding layer and a lightweight modified epoxy asphalt concrete upper layer.
2. The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claim 1 is characterized in that: The thickness of the lower layer of the lightweight flexible cast asphalt concrete is 3 to 4.5 cm, and the thickness of the upper layer of the lightweight modified epoxy asphalt concrete is 2 to 3.5 cm.
3. The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claim 1 is characterized in that: The lower layer of the lightweight flexible cast asphalt concrete comprises the following components, calculated by weight: 5 to 15 parts of cast asphalt binder, 75 to 85 parts of mineral material, 1 to 4 parts of composite fiber and 0.3 to 1.2 parts of natural mineral powder type warm mix agent; wherein the mineral material comprises mineral powder, lightweight aggregate and ordinary aggregate.
4. The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claim 3 is characterized in that: The cast asphalt binder is composed of SBS modified asphalt and lake asphalt in a mass ratio of (6.5:3.5) to (8:2).
5. The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claim 3 is characterized in that: The composite fiber is composed of one or more of steel fiber, carbon fiber, glass fiber, polypropylene fiber, nylon fiber and plant fiber, and has a length of 5-15 mm and a diameter of 0.1-0.5 mm.
6. The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claim 3 is characterized in that: The lightweight flexible cast asphalt mixture is divided into particle grading levels using sieve holes of diameters of 0.075-0.15 mm, 0.6-1.18 mm, 2.36-4.75 mm and 9.5-13.2 mm as dividing lines, thereby achieving multiple grading combinations.
7. The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claim 1 is characterized in that: The crushed stone spread on the lower layer of the lightweight flexible cast asphalt concrete is composed of one or more of granite, basalt or diabase, the crushed stone particle size is 12-18 mm, and the spreading amount is 8-12 kg / m 2 .
8. The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claim 1 is characterized in that: The high-viscosity lightweight epoxy resin bonding layer includes component A and component B. Calculated by weight, component A includes the following ingredients: 50-110 parts of bisphenol A or bisphenol F epoxy resin, 5-25 parts of toluene glycidyl ether active diluent, 2-4 parts of aluminate active coupling agent, and 0.3-2 parts of polyether defoamer; component B includes the following ingredients: 45-120 parts of epoxy resin toughening curing agent, 65-130 parts of matrix asphalt, 8-20 parts of polypropylene glycol diglycidyl ether active toughening agent, and 3-10 parts of lightweight filler.
9. The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claim 8 is characterized in that: The light filler is composed of any one or more of light calcium carbonate, expanded perlite, hollow glass microspheres, natural coal gangue and clay ceramsite.
10. The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claim 1, characterized in that: The lightweight modified epoxy asphalt concrete comprises the following components, calculated in parts by weight: 2 to 10 parts of modified epoxy resin binder, 10 to 15 parts of epoxy asphalt, 5 to 8 parts of granite asphalt, 15 to 140 parts of ordinary aggregate, 12 to 120 parts of lightweight aggregate, and 17 to 35 parts of mineral powder; wherein the modified epoxy resin binder is made of bisphenol A or bisphenol F type epoxy resin and modified amine curing agent in a mass ratio of 4 to 5:
1.
11. A semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claims 3 and 10, characterized in that: The mineral powder is ground from limestone; the lightweight aggregate is divided into light coarse aggregate and light fine aggregate, and is composed of 700-grade porous volcanic rock ceramsite, wherein the particle size range of the light coarse aggregate is 6-15 mm, and the particle size range of the light fine aggregate is 0-5 mm; the ordinary aggregate is formed by crushing basalt, and the mass percentage of the lightweight aggregate replacing the ordinary aggregate is 1%-99%.
12. The semi-rigid and semi-flexible lightweight steel bridge deck pavement structure according to claim 10, characterized in that: The oil-to-stone ratio of the lightweight modified epoxy asphalt concrete is 5-12%.
13. A paving method for a semi-rigid and semi-flexible lightweight steel bridge deck pavement structure, characterized in that: The specific implementation steps are as follows: S1. Sandblast the steel plate to remove rust, so as to obtain a steel panel with a cleanliness greater than Sa2.5 and a roughness of 70-150 μm, and then spray epoxy zinc-rich anti-rust paint with a thickness of 80-150 μm; S2. After the bonding strength of the epoxy zinc-rich anti-rust paint is greater than 7 MPa, clean the surface and apply epoxy resin adhesive type II to form a waterproof bonding layer. The coating amount is 0.4~0.5 kg / m 2 ; S3. Prepare lightweight flexible poured asphalt concrete, and then evenly spread it on the waterproof bonding layer with a thickness of 3-4.5 cm by a paver. The longitudinal spacing between the pavers is 5-20 m, the paving rate is 1.8-3.0 m / min, and the paving temperature is controlled above 160°C. For local areas where machinery cannot operate, manual paving is used; S4. Use a mixed asphalt consisting of modified SBS asphalt and lake asphalt to wrap the crushed stones with a particle size of 12-18 mm. 2 The amount of mixed asphalt is evenly spread on the surface of lightweight flexible cast asphalt concrete, and then rolled 2 to 4 times with a 20 to 30 t rubber-wheel roller to make the crushed stones half-embedded in the concrete layer; wherein the mixed asphalt accounts for 0.3 to 1.5% of the mass of the crushed stones; S5. Prepare a high-viscosity lightweight epoxy resin adhesive. After the lower layer of lightweight flexible cast asphalt concrete reaches the curing time, apply 0.55~0.9 kg / m 2 Apply the coating evenly; S6. Prepare lightweight modified epoxy asphalt concrete and use a paver to evenly spread it with a thickness of 2 to 3.5 cm on the lower layer of lightweight flexible cast asphalt concrete coated with a high-viscosity lightweight epoxy resin binder. Then use an 18 to 30 t steel and rubber-wheel roller to compact it 6 to 9 times to complete the rolling. Finally, carry out 2 to 7 days of maintenance depending on the change in the rebound strength value of the concrete. When the rebound strength value stabilizes at 40 to 60 MPa, it can be opened to traffic.